Insight into oral amphiphilic cyclodextrin nanoparticles for colorectal cancer: comprehensive mathematical model of drug release kinetic studies and antitumoral efficacy in 3D spheroid colon tumors - Sedat Ünal; Gamze Varan; Juan M. Benito; Yeşim Aktaş; Erem Bilensoy (Beilstein Journal of Organic Chemistry, 2023)
Colorectal cancer (CRC) is the third most diagnosed cancer type globally and ranks second in cancer-related deaths. With the current treatment possibilities, a definitive, safe, and effective treatment approach for CRC has not been presented yet. However, new drug delivery systems show promise in this field. Amphiphilic cyclodextrin-based nanocarriers are innovative and interesting formulation approaches for targeting the colon through oral administration. In our previous studies, oral chemotherapy for colon tumors was aimed and promising results were obtained with formulation development studies, mucin interaction, mucus penetration, cytotoxicity, and permeability in 2D cell culture, and furthermore in vivo antitumoral and antimetastatic efficacy in early and late-stage colon cancer models and biodistribution after single dose oral administration. This study was carried out to further elucidate oral camptothecin (CPT)-loaded amphiphilic cyclodextrin nanoparticles for the local treatment of colorectal tumors in terms of their drug release behavior and efficacy in 3-dimensional tumor models to predict the in vivo efficacy of different nanocarriers. The main objective was to build a bridge between formulation development and in vitro phase and animal studies. In this context, CPT-loaded polycationic-β-cyclodextrin nanoparticles caused reduced cell viability in CT26 and HT29 colon carcinoma spheroid tumors of mice and human origin, respectively. In addition, the release profile, which is one of the critical quality parameters in new drug delivery systems, was investigated mathematically by release kinetic modeling for the first time. The overall findings indicated that the strategy of orally targeting anticancer drugs such as CPT with positively charged poly-β-CD-C6 nanoparticles to colon tumors for local and/or systemic efficacy is a promising approach.